Backward Design : Strategi Pembelajaran dalam Meningkatkan Keterlibatan Siswa - Mulyani, Ayu Ariyana; Setiadi, Elly Malihah; Nurbayani, Siti (Jurnal Paedagogy, 2023)
This research aims to explore the backward design model as a learning strategy to enhance student engagement. This research adopts a descriptive approach with a qualitative method. The participants of this study were high school teachers selected through the snowball sampling technique. The data collection was conducted through interviews and participatory observation, while data analysis follows an interactive model analysis approach, including data reduction, data display, and conclusion drawing/verification. The research findings indicated that the backward design was one of the effective learning design models as it focused on understanding and developing students' thinking skills. The model directed teachers to set learning objectives that wereappropriate to the student's needs and skills, conduct assessments to measure students' understanding and skills and formulate when delivering materials or certain concepts gradually. Implementing concept-checking techniques allows teachers to measure students' understanding periodically, and applying interaction patterns accommodates continuous interactions.Â  Â 